2022
DOI: 10.1007/s12223-022-00958-5
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of seed-associated bacteria and fungi on staple crops using the cultivation and metagenomic approaches

Abstract: One of the key factors affecting seed quality is microbial communities residing on and in the seeds. In this study, microbial populations of seeds of conventionally and organically produced wheat, barley, and maize were analyzed using two different approaches: the cultivation method and metagenomics. For cultivation, three basic media were used: DG18 (for fungi), and nutrient agar or tryptic soy agar supplemented with cycloheximide or nystatin (for bacteria). Metagenomic sequencing was performed using the Illu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
13
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 39 publications
3
13
1
Order By: Relevance
“…From these projects, the abundant genera found concerning wheat endophytes were Bacillus, Stenotrophomonas, Pseudomonas, Acinetobacter, Enterobacter, Clostridium, and Xanthomonas. The previous experiment, carried out by Tkalec et al (2022), supported our findings, where they observed abundance of Bacillus species in their samples. The bacterial genera Clostridium and Xanthomonas were excluded from community formation due to their pathogenic nature for plants and animals.…”
Section: Discussionsupporting
confidence: 86%
“…From these projects, the abundant genera found concerning wheat endophytes were Bacillus, Stenotrophomonas, Pseudomonas, Acinetobacter, Enterobacter, Clostridium, and Xanthomonas. The previous experiment, carried out by Tkalec et al (2022), supported our findings, where they observed abundance of Bacillus species in their samples. The bacterial genera Clostridium and Xanthomonas were excluded from community formation due to their pathogenic nature for plants and animals.…”
Section: Discussionsupporting
confidence: 86%
“…As shown in Figure 4A,B, Curtobacterium, Bacillus and Pantoea are the most abundant bacterial genera, while Aureobasidium, Fusarium and Alternaria are the richest in fungal genera. However, a bit different from the previous reports, it was found that wheat and maize are mainly composed of three bacterial genera (Bacillus, Paenibacillus Curtobactreium) and one fungal, Aspergillus, based on both sequencing and culturing techniques (Tkalec et al, 2022). In addition, wheat and maize share only less than 10% microbial population under both conventional and organic farming systems.…”
Section: What Are These Seed Microbes?contrasting
confidence: 61%
“…Generally, the relative content was bacteria > fungi > protozoa > viruses, but in maize kernels and roots, the relative content of fungi exceeded that of bacteria. In general, numerous studies have shown that bacteria are the predominant of all microorganisms [45][46][47], but the results of the new analysis strategy showed the composition of various types of microorganisms, from which it can be seen that eukaryotic microorganisms, including fungi and protozoa, sometimes dominate in specific tissues. In addition, protozoa are generally not a hot spot for research on plant endophytic microorganisms; however, in this study, we note that the relative content of protozoa should not be neglected, as they may also play an important role in promoting plant growth and other aspects.…”
Section: Discussionmentioning
confidence: 99%